The Effect of the Use of Blended Learning-Assisted Learning Module on Learning Outcomes - R, OsmiZein; Iskarni, Paus (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
The burden of Education Law No. 20/2003 article 1 paragraph 1 education forms students to actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, nation, and country. To achieve this goal the teachermust be professional to create a conducive learning atmosphere for the creation of maximum learning. For the social studies field of junior high school, the study load to be achieved by students is very dense so the teacher feels overwhelmed in conveying all the material. For this reason, a way must be found so that all existing material can be conveyed in full. And the Blended Learning learning model with the help of E-Modules is very appropriate. With the E-module that uses IT, students can learn repeatedly until they can understand and understand.Keywords:Blended Learning, E Module, Learning Outcomes